Masculinity, Islamism, and Post-Islamism: A Case Study of Da’wah Tarbiyah Activists in Yogyakarta and Surakarta - Gun Gun Gunawan (Arabic Literature Department, 2020)
As a movement which is related to the Muslim Brotherhood in Egypt, the Tarbiyah movement carries Islamist agendas which indirectly influence the concept of masculinity adopted by its activists. This research examines the concept of masculinity adopted by campus da'wah activists affiliated with the Tarbiyah movement in the city of Yogyakarta and Surakarta. The research subjects were campus da'wah activists at Universitas Gadjah Mada Yogyakarta and Universitas Sebelas Maret Surakarta. The results showed that the concept of masculinity adopted by Tarbiyah da'wah activists experienced a shift in purpose. Now the concept of masculinity is constructed not to support the jihad agenda, but to form an Islamic society that has a good standard of living such as being healthy, strong, intelligent, prosperous, and able to carry out its role properly as an individual, family member, community and nation.